2022
DOI: 10.1172/jci.insight.155848
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 controls hepatic lipid metabolism via sex-dependent interorgan crosstalk

Abstract: The liver regulates energy partitioning and utilization in a sex-dependent manner, coupling hepatic substrate availability to female reproductive status. Fibroblast growth factor-21 (FGF21) is a hepatokine produced in response to metabolic stress that adaptively directs systemic metabolism and substrate utilization to reduce hepatic lipid storage. Here we report that FGF21 alters hepatic transcriptional and metabolic responses, and reduces liver triglycerides, in a sex-dependent manner. FGF21 decreased hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…These included: 'Folate metabolism', 'Catecholamine biosynthesis', 'Thyroid hormone synthesis', 'Tyrosine metabolism', and 'Arachidonic acid metabolism'. In agreement with our recent report that the effect of FGF21 to reduce hepatic and adipose tissue triglycerides is more apparent in male mice compared to female littermates (38), the top-five most enriched pathways in males were related to lipid metabolism (Fig. 2A).…”
Section: Fgf21 and Skeletal Muscle Atrophysupporting
confidence: 92%
See 2 more Smart Citations
“…These included: 'Folate metabolism', 'Catecholamine biosynthesis', 'Thyroid hormone synthesis', 'Tyrosine metabolism', and 'Arachidonic acid metabolism'. In agreement with our recent report that the effect of FGF21 to reduce hepatic and adipose tissue triglycerides is more apparent in male mice compared to female littermates (38), the top-five most enriched pathways in males were related to lipid metabolism (Fig. 2A).…”
Section: Fgf21 and Skeletal Muscle Atrophysupporting
confidence: 92%
“…Recent work by ourselves and others revealed that the benefit of FGF21 for hepatic lipid metabolism is sex dependent. FGF21 decreased liver triglycerides in obese male mice, but this was abrogated among obese female littermates (38,39). Thus, sex is an important biological variable influencing FGF21 physiology.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The reduction in body weight of males was attributed to decreased fat mass, as was true for our study. Interestingly, in their study food intake was also increased in female and not male mice upon FGF21 treatment, which was fully reversed in ovariectomized and aged female mice 47 . These results strongly suggest that the effects of FGF21 administration to decrease body weight are counteracted by ovarian/sex hormones and this leads to increased food intake, as we observed as well.…”
Section: Discussionmentioning
confidence: 85%
“…For instance, in A y mice, females were resistant to weight loss and their food intake was increased upon FGF21 treatment, which was in stark contrast with the effects in males 46 . Later, Chaffin et al showed that administration of FGF21 triggers body weight loss in male C57BL/6J, but not female mice, even though circulating FGF21 levels in plasma were similar between sexes 47 . The reduction in body weight of males was attributed to decreased fat mass, as was true for our study.…”
Section: Discussionmentioning
confidence: 99%